Reed-Solomon codes and their applications - Wicker, Stephen B.; Bhargava, Vijay K. (IEEE Press, 1994)
Reed-Solomon codes provide critical error control for many different types of digital communications systems, including those on the Voyager spacecraft and in CD players. This collection of 13 articles from leading researchers in the field provides a comprehensive overview of the history and practical applications--some never before published--of these